ANALISA LIFEBOAT PLACEMENT EFFECTIVENESS TERHADAP PROSES EVAKUASI KAPAL PENUMPANG MENGGUNAKAN METODE AGENT BASED MODELLING SIMULATION - Imam Pujo Mulyatno; Parlindungan Manik; Shalwa An-nisa Addawiyah (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The study of â€œLifeboat placement effectivenessâ€ which was applied to the evacuation process of passenger ships should be based on the regulation of IMO MSC.1/Circ.1533. The analysis of the evacuation duration was important considering the high number of fatalities in shipping accidents based on KNKT data, as many as 686 people died in the last 7 years. This study analyzed the duration of evacuation using a simulation method based on â€œAgent Based Modelling Simulationâ€ with the purpose to obtain a modeling framework to simulate the evacuation process to the lifeboat in 3 dimensions. Simulations were applied to 4 cases with 2 different lifeboat positions. The results of the analysis showed that the total value of the evacuation duration for lifeboats placement on the navigation deck which was placed close to the main stair of the exit route was leading than the placement in the existing position, which as case 1 lead by 1 minute, case 2 lead by 1 minute 2 seconds, case 3 lead by 23 seconds, and case 4 a lead by 17 seconds. The calculation also showed that the total evacuation duration in each case was valued at 60 minutes, which met the IMO MSC.1/Circ.1533 standard.